Next-generation biostimulants: molecular insights, digital integration, and regulatory frameworks for sustainable agriculture - Mashabela, Manamele D.; Terefe, Tarekegn; Kerchev, Pavel; Sitole, Lungile; Mhlongo, Msizi I. (Frontiers in Plant Science, 2025)
The development of biostimulants is undergoing a critical evolution, shifting from empirical applications toward precisely engineered solutions. However, this transition is hampered by fundamental gaps, inclusive of: (1) the absence of temporal-technological frameworks connecting biostimulants development with broader agricultural revolutions, (2) insufficient mechanistic understanding linking molecular modes of action to precision application strategies, and (3) unclear regulatory frameworks and integration pathways for biostimulants within digital agriculture ecosystems (AI/IoT). This review synthesises the evolution of biostimulants through a generational framework (1.0-4.0) and examines their integration with Agriculture 5.0 technologies. We analyse classifications, molecular mechanisms, and regulatory frameworks while evaluating omics-driven precision biostimulant formulations for AI/IoT integration. Our analysis suggests that successful integration requires coordinated molecular validation, regulatory harmonisation, and digital platform development, providing researchers and policymakers with a roadmap for advancing biostimulants science from fragmented research toward systematic, technology-enabled solutions for climate-smart and sustainable agriculture, in line with SDGs 2, 13, and 15.